A replication-incompetent adenoviral vector encoding for HSV-2 gD2 is immunogenic and protective against HSV-2 intravaginal challenge in mice. - Elisa Rossetti; Marija Vujadinovic; Ella van Huizen; Jeroen Tolboom; Hanneke Schuitemaker; Feng Yao; Roland Zahn; Eirikur Saeland (PLoS ONE)
Herpes Simplex virus (HSV) is the cause of genital herpes and no prophylactic treatment is currently available. Replication-incompetent adenoviral vectors are potent inducers of humoral and cellular immune responses in humans. We have designed an adenoviral vector type 35 (Ad35)-based vaccine encoding the HSV-2 major surface antigen gD2 (Ad35.HSV.gD2). Immunization of mice with Ad35.HSV.gD2 elicited virus neutralizing antibody titers (VNT) and cellular responses against HSV-2 and HSV-1. While immunity was lower than for CJ2-gD2, both vaccines showed 100% survival against intravaginal challenge with HSV-2 G strain and a strong inverse correlation was observed between HSV-2 infection (as measured by viral shedding) and VNT. A combination of Ad35.HSV.gD2 with Ad35 encoding for gB2 (Ad35.HSV.gB2) resulted in increased VNT and lower infection, compared with Ad35.HSV.gD2 alone. Transfer of immune serum into naïve BALB/c mice before intravaginal challenge confirmed the role of antibodies in the protection of mice against infection although other immune factors may play a role as well.